Predictors of anemia in pregnant women residing in rural areas of the Oromiya region of Ethiopia. - Zillmer, Krista.; Pokharel, Ashish.; Spielman, Kathryn.; Kershaw, Meghan.; Ayele, Kidane.; Kidane, Yitbarek.; Belachew, Tefera.; Houser, Robert F.; Kennedy, Eileen.; Griffiths, Jeffrey K.; Ghosh, Shibani. (2017)
Background: Anemia in pregnancy is associated with higher risk of low birth weight and both maternal and perinatal mortality. While previous studies in Ethiopia have examined factors associated with anemia, which factors are the most important determinants of anemia in this population remain unclear. The objective of this study was to examine the association between anemia status in pregnant women with different health, behavioral, and socioeconomic factors in Oromiya province of Ethiopia.; Keywords: Pregnancy, Anemia, Ethiopia, Maternal, Nutrition.; Springer Open.